2022
DOI: 10.1007/s10639-022-11004-9
|View full text |Cite
|
Sign up to set email alerts
|

Learning with the interactive whiteboard in the classroom: Its impact on vocabulary acquisition, motivation and the role of foreign language anxiety

Abstract: When used in a sensible way, Interactive Whiteboards (IWB) are supposed to motivate and engage students in learning in the classroom. Thereby, they might also stimulate students who are usually more restrained, such as more anxious students. However, the body of research on the impact of IWB lessons is rather small. The present study investigated whether a 45-minute lesson with the IWB compared to a conceptual identical 45-minute lesson without the IWB would support learning and motivation within the subject E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…In EFL educational contexts, the IWB has a noticeable influence on learning a foreign language (Kühl & Wohninsland, 2022). To highlight the impact of the IWB on foreign language school classes, Gray et al (2005) concluded that what makes learners concentrate more on structures like reflexive pronouns, negative statements, and different forms of grammatical categories such as nouns and adjectives is the application of visual components that include animation in addition to the color features.…”
Section: The Contribution Of Iwb To the Learning Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In EFL educational contexts, the IWB has a noticeable influence on learning a foreign language (Kühl & Wohninsland, 2022). To highlight the impact of the IWB on foreign language school classes, Gray et al (2005) concluded that what makes learners concentrate more on structures like reflexive pronouns, negative statements, and different forms of grammatical categories such as nouns and adjectives is the application of visual components that include animation in addition to the color features.…”
Section: The Contribution Of Iwb To the Learning Processmentioning
confidence: 99%
“…The interactive whiteboard (IWB), among these technologies, is recognized as a large touch-sensitive board that, in conjunction with a computer and a digital projector, displays images on its screen (Erdener, 2021;Smith et al, 2005). When used judiciously, the IWB is expected to enhance learners' motivation and engagement within classrooms (Kühl & Wohninsland, 2022), given that both learners and instructors can control and manipulate programs via its interactive screen (Guzmán et al, 2013), particularly within EFL settings. Therefore, integrating the IWB into EFL classrooms is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Areté, Revista Digital del Doctorado en Educación. 10 ( 19), 183 -202. https://doi.org/10.55560/arete.2024.19.10.10 operatividad destacada de aplicativos informáticos, sino también contribuir al bienestar socio emocional de los estudiantes considerando un correcto andamiaje para guiar y monitorear el desenvolvimiento activo de los educandos en los entornos virtuales, la trayectoria sociocultural para una mejor adaptación, la adquisición gradual y significativa de nuevos núcleos temáticos y la exploración de entornos de trabajo cooperativo (Fajardo-Santamaría, 2022; Kühl & Wohninsland, 2022;Bastarrachea et al, 2023).…”
Section: Instrumento Y Procedimientosunclassified
“…Furthermore, the study discovered students who utilized the ISB reported better levels of motivation and engagement. Davidovitch et al (2017) and Kühl et al (2022) investigated the impact of ISB on student motivation and engagement. The study found that using ISB in the classroom boosted student engagement and motivation.…”
Section: Interactive Smart Board (Isb) Effect On Students' Achievemen...mentioning
confidence: 99%